"National context, school factors, and individual teacher characteristics: Which matters most for teacher collaboration?". (December 2022) - Liu, Yan; Benoliel, Pascale
Abstract: Merging the variables from the 2018 TALIS, the 2018 PISA, and the 2004 GLOBE study, the present research investigates the associations between contextual variables and teacher collaboration across national boundaries, which is essential to understand teacher collaboration in a broader context. Employing multi-level linear models, this study specified the variance in teacher collaboration related to teacher characteristics, school factors, and country policy and cultural variations, respectively. The results revealed that the teacher-level factors are associated with a significant proportion of variance in the outcome. Meanwhile, school culture, leadership, student composition, and country-level policy are influential for teacher collaboration. Highlights: This study used the variables from the 2018 TALIS, the 2018 PISA, and the 2004 GLOBE. Taking advantage of multiple datasets to study the influential factors for teacher collaboration across national boundaries. Employing robust quantitative analyses to examine how teacher, school, and country variables influence teacher collaboration. The results reveal that teacher-level factors are associated with a large proportion of variance in teacher collaboration. School culture, school leadership, and country-level policy could be influential for teacher collaboration.